2019
DOI: 10.1080/21691401.2019.1671428
|View full text |Cite|
|
Sign up to set email alerts
|

Fyn gene silencing reduces oligodendrocytes apoptosis through inhibiting ERK1/2 phosphorylation in epilepsy

Abstract: This study aimed to investigate the effect of Fyn gene silencing on the apoptosis of oligodendrocytes (OLs) in epileptic model in vitro and the involved mechanism. Primary oligodendrocyte pro-genitor cells (OPCs) were separated from rats and differentiated to OLs. Immunofluorescent labeling showed positive expression of A2B5 in OPCs and Olig2 in OLs, suggesting the successful separation of OPCs and OLs. Three Fyn siRNAs (si-Fyn) and Fyn siRNA negative control (NC) were transfected into OLs. Western blot showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Fyn in neuron is known to modulate both NMDA and GABA A receptors and is associated with both excitatory and inhibitory ion channels, which are potentially associated with the onset of seizure [5,12,13]. Silencing of the Fyn gene reduced oligodendrocyte apoptosis in an epileptic model in vitro [14], and previous studies have suggested that Fyn is closely related to epilepsy. Thus, inhibiting Fyn may be a possible treatment for epilepsy.…”
Section: Introductionmentioning
confidence: 94%
“…Fyn in neuron is known to modulate both NMDA and GABA A receptors and is associated with both excitatory and inhibitory ion channels, which are potentially associated with the onset of seizure [5,12,13]. Silencing of the Fyn gene reduced oligodendrocyte apoptosis in an epileptic model in vitro [14], and previous studies have suggested that Fyn is closely related to epilepsy. Thus, inhibiting Fyn may be a possible treatment for epilepsy.…”
Section: Introductionmentioning
confidence: 94%
“…It is reported that the Fyn was upregulated in the microglia and oligodendrocytes in hippocampus during epileptogenesis. Silencing Fyn will suppress epileptogenesis through reduce neuroinflammatiom and apoptosis [30,31]. All these results indicate that SELENBP1 and GRIPAP1 in HS ILAE type 1 may affect the regeneration of neurons compared with these in no-HS type; however, this aspect of the study has not been reported yet.…”
Section: Discussionmentioning
confidence: 86%
“…It is reported that the Fyn was upregulated in the microglia and oligodendrocytes in the hippocampus during epileptogenesis. Silencing Fyn will suppress epileptogenesis through reduce neuroin ammatiom and apoptosis (Sharma et al 2018;Luo et al 2020). All these results indicate that SELENBP1 and GRIPAP1 in HS ILAE type 1 may affect the regeneration of neurons compared with those in no-HS type; however, this aspect of the study has not been reported yet.…”
Section: Discussionmentioning
confidence: 86%